Intermedialität in nuce – „Das Fräulein von Scuderi” in der Comicfassung - Kupczyńska, Kalina (Studia Germanica Posnaniensia, 2014)
The essay reflects on intermedial explorations of literary texts in the comics. Under the first heading, the essay briefly notes how the term ‘intermediality’ has been considered in the literary criticism and in comic studies. It then focusses on the analysis of E.T.A. Hoffmann’s Das Fräulein von Scuderi (1819), particularly on the reception and on the narrative structure of the text. Under the second heading, the essay explores the adaptation of Hoffmann’s text in the comic by Alexandra Kardinar and Volker Schlecht (2011). It argues that the adaptation highlights the ‘popular’ aspects of the literary text, using various devices of the language of comics.